Searching for the Past, Writing for the Present:: Charles Ryle Fay and Newfoundland’s Contested Past - Ludlow, Peter (Acadiensis, 2010)
Abstract In the autumn of 1953 the Cambridge economic historian, C.R. Fay, presented a series of lectures at Memorial University based on his tours of the province. As a collector of all things Newfoundland and an observer of island’s shifting place within empire, Fay laid the foundation for a cultural renaissance in Newfoundland studies. Ultimately, however, the scope of his project, his personal bias, and indifference to the island’s historiography undermined his research and his significance as a historian of Newfoundland.